A water-soluble two-photon ratiometric triarylboron probe with nucleolar targeting by preferential RNA binding. Issue 83 (6th October 2017) - Liu, Jun; Zhang, Shilu; Zhang, Chenghua; Dong, Jun; Shen, Chengyi; Zhu, Jiang; Xu, Huajun; Fu, Mingkai; Yang, Guoqiang; Zhang, Xiaoming
Abstract : By functionalizing triarylboron with cyclen, we developed a water-soluble two-photon ratiometric triarylboron probe with nucleolar targeting by preferential RNA binding. Abstract : By functionalizing triarylboron with cyclen, we developed a two-photon fluorescence probe, TAB-2, which can selectively bind RNA with a ratiometric readout. We testedTAB-2 in NIH/3T3 fibroblast cells, and demonstrated its capability in visualizing nucleoli and analyzing microenvironment polarity by two-photon and fluorescence-lifetime imaging microscopy.